2012
DOI: 10.1111/j.1466-8238.2012.00795.x
|View full text |Cite
|
Sign up to set email alerts
|

The world and its shades of green: a meta‐analysis on trophic cascades across temperature and precipitation gradients

Abstract: AimTo assess effects of current global temperature and precipitation gradients on the trophic function of plant-herbivore-predator interactions. Specifically, I study effects of climatic gradients on factors that control herbivore abundances: topdown, bottom-up trophic cascades and plant defences. I include predictions of climate change on shifts in trophic function, under the assumption that temperature and precipitation affect the physiology and performance of plants, herbivores and predators. Location Globa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
76
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(84 citation statements)
references
References 47 publications
6
76
2
Order By: Relevance
“…For example, Rodriguez-Castañeda (2012) was able to greatly increase the number of tropical ecological studies in her meta-analysis by including papers published in Spanish and Portuguese. Not only are potentially vital instances or example of invasion going unexamined that could advance the science, but serious future ecological or economic harms may be unrecognized in understudied regions where the impact of human activities is increasing.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Rodriguez-Castañeda (2012) was able to greatly increase the number of tropical ecological studies in her meta-analysis by including papers published in Spanish and Portuguese. Not only are potentially vital instances or example of invasion going unexamined that could advance the science, but serious future ecological or economic harms may be unrecognized in understudied regions where the impact of human activities is increasing.…”
Section: Discussionmentioning
confidence: 99%
“…In search for factors that underlie the documented biogeographic gradient, we ask for more research on how associational effects depend on and follow global gradients in i) regional species diversity of herbivores and host plants, ii) herbivore density and pressure, especially during times of outbreaks [25, 2830, 5256], iii) herbivore specialization [4, 5, 8, 9, 20, 57], iv) tree defences [25, 27, 29, 31, 52, 58] and v) abiotic factors affecting tree or herbivore development (e.g. precipitation, climate stability, CO 2 -concentration, UVB-radiation).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies also found that global gradients exist for plant species richness [21, 22], herbivore species richness [2325], plant defences [26, 27], herbivore pressure [25, 28, 29], leaf herbivory [30] and trophic interactions [31]. Since temperature is a key driver of herbivore development and abundance [32], consumption rates [33] and host-plant choices [34] it is likely to influence these plant-herbivore interactions [33, 34].…”
Section: Introductionmentioning
confidence: 99%
“…Although we show that the diet breadth of herbivore assemblages predicts the strength of indirect effects of plant damage for individual plant species [species-level cascades sensu (43)], we further suggest that differences in the dietary specialization of herbivores among ecosystems (18) might inform variation among ecosystems in the strength of trophic cascades (44,45). For example, some of the unexplained variation in top-down control of plant production in terrestrial vs. aquatic (5,46) and managed vs. unmanaged (46) ecosystems could be explained by the observed differences between these systems in herbivore diet breadth.…”
Section: Discussionmentioning
confidence: 99%